Effect of Transtibial Prosthesis Mass Alteration on Metabolic Activity and Outcomes. Issue 1 (January 2022) - Seth, Mayank; Warren, Kelly A.; Lamberg, Eric M.
ABSTRACT: Introduction: The loss of a lower limb is a traumatic life-changing event. It imposes restrictions on an individual's mobility and adversely affects his/her personal and social life. The gait of an individual with transtibial amputation (TTA) is less efficient, as evidenced by the higher metabolic cost during walking compared with individuals without amputation. The mass of a prosthetic leg may influence the metabolic cost of the user and potentially impact his/her activity. Currently, however, limited evidence is available on transtibial prosthesis mass. Hence, the purpose of this study was to explore the effects of prosthesis mass alterations on metabolic cost, function, satisfaction, and health-related quality of life of individuals with TTA after 7 days of acclimation. Materials and Methods: A repeated-measures study involving three testing sessions (each 1 week apart) was conducted, during which three load conditions were examined. At the end of the first two sessions, participant's prosthesis mass was increased by adding either 30% (light load) or 50% (heavy load) of the total mass difference between both legs to a proximal location on the prosthesis. Data collection during each session comprised a 6-minute walk test (during which metabolic activity was also acquired) and completion of questionnaires from the Orthotics and Prosthetics Users' Survey. Results: Increasing prosthesis mass with the light and heavy load conditions did not significantly increase the net metabolic cost and walking economy of the participants. Participant function (performance and self-reported) and satisfaction were not significantly affected by the mass increase. However, while using the light load condition, participants reported a significant improved health-related quality of life. Conclusions: Increasing prosthesis mass did not result in the worsening of metabolic activity and other selected outcomes among people with TTA.